Visual Information for digital inclusion process in hybrid libraries and librarians' action - Silva, Rafaela Carolina da [UNESP]; Vicentini Jorente, Maria Jose; Caldas, Rosangela Formentini; Nakano, Natalia (Univ Nacional Autonoma Mexico, 2018)
The set of actions and cultural conditions of a society produce information in such a way to act directly on the development and use of services and goods by this society. Digital inclusion and the use of images is encouraged as converging languages within hybrid libraries. We aimed to study attractive resources provided by visual language in social and digital inclusion processes. Therefore, we carried out a literature review on the syntax of visual languages. As a result, a Guide for Librarians was constructed. We concluded that understanding and using images serve as a convergence for those who experience them.
Keywords: Information and Technology; Visual Information; Visual Languages; Digital Inclusion